2019
DOI: 10.1093/ejcts/ezz082
|View full text |Cite|
|
Sign up to set email alerts
|

Simplified frozen elephant trunk technique for combined open and endovascular treatment of extensive aortic diseases

Abstract: OBJECTIVES: This study aims to analyse the impact of a simplified frozen elephant trunk (FET) technique on early outcome. METHODS: Between October 2010 and August 2018, 92 consecutive patients (mean age 64.4 ± 12.2 years) underwent FET surgery. Underlying pathologies were thoracic aneurysm in 35 patients, acute aortic dissection in 25 patients and chronic dissection in 32 patients. Thirty patients underwent a simplified FET t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 15 publications
2
60
0
Order By: Relevance
“…The Bologna group noted a postoperative SPI to be higher in those who underwent Z-3-FET versus Z-2-FET (7.5% versus 1.4%, respectively), however, this difference was not significant. 24 A similar outcome was reported by Tsagakis et al, 22 where the rate of paraplegia was reduced to half in the Z-2-FET patients, but in their cohort the difference was also deemed not significant. The same team are also noted that the incidence of stroke resulting in paraplegia are 50% lower with Z-2-FET approach.…”
Section: Spinal Cord Injury (Spi)supporting
confidence: 80%
“…The Bologna group noted a postoperative SPI to be higher in those who underwent Z-3-FET versus Z-2-FET (7.5% versus 1.4%, respectively), however, this difference was not significant. 24 A similar outcome was reported by Tsagakis et al, 22 where the rate of paraplegia was reduced to half in the Z-2-FET patients, but in their cohort the difference was also deemed not significant. The same team are also noted that the incidence of stroke resulting in paraplegia are 50% lower with Z-2-FET approach.…”
Section: Spinal Cord Injury (Spi)supporting
confidence: 80%
“…Preventza et al 6 found that a stent length of 10 cm had a lower risk of spinal cord ischemia, and a stent≥ 15 cm or beyond the T8 should be avoided during the FET operation. Also, the deployment of stent‐graft in Zone 2 can reduce the visceral ischemia time and it is technically easier compared to anastomoses in Zone 3, which can lead to decreased neurological adverse events 25 . We also found in meta‐regression analysis that age was associated with cerebrovascular accidents.…”
Section: Discussionmentioning
confidence: 53%
“…A total of 15 studies reported the number of patients implanted the FET stent with the distal anastomosis in Zones 2 or 3, of which only 3 studies including 660 patients compared outcomes in groups by Zone 2 versus Zone 3 25,46,66 . A total of 282 and 378 patients were implanted the FET stent with the distal anastomosis in Zone 2 and Zone 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximal aortic surgery comprised aortic root replacement procedures including the aortic-valve-sparing techniques according to David or to Yacoub, and composite valve grafting procedures according to Bentall comprising aortic root replacement with a biological valve or with a mechanical valve as described previously [39] ( Table 3). Five of these procedures carried out in Marfan syndrome extended into the aortic arch with usage of a frozen elephant trunk procedure in three as described previously [40] (Table 3). For distal aortic repair we employed open techniques with surgical placement of a prosthesis in the isolated thoracic aortic segment, or in the thoracoabdominal segment, or in the abdominal aorta.…”
Section: Clinical Eventsmentioning
confidence: 99%